2019
DOI: 10.1002/ardp.201900238
|View full text |Cite
|
Sign up to set email alerts
|

Benzo[4,5]thieno[2,3‐d]pyrimidine phthalimide derivative, one of the rare noncompetitive inhibitors of dipeptidyl peptidase‐4

Abstract: A small library of benzo[4,5]thieno[2,3‐d]pyrimidine phthalimide and amine derivatives was evaluated for inhibitory activity against dipeptidyl peptidase‐4 (DPP‐4). The phthalimide derivatives exhibited better activity than the amine precursors, with 2‐(2‐(3‐chlorobenzyl)‐5,6,7,8‐tetrahydrobenzo[4,5]thieno[2,3‐d]pyrimidin‐4‐yl)isoindoline‐1,3‐dione (compound 14) as the most effective inhibitor (IC50 = 34.17 ± 5.11 μM). The five most potent selected inhibitors did not show cytotoxicity to a greater extent on Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Most of the DPP4 inhibitors in the market are competitive inhibitors, e. g., alogliptin, linagliptin, saxagliptin, sitagliptin, and vildagliptin [1,16,23]. On the contrary, several inhibitors were reported as noncompetitive inhibitors in vitro [21,24], which indicated the availability of allosteric sites in the DPP4 binding pocket [24].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the DPP4 inhibitors in the market are competitive inhibitors, e. g., alogliptin, linagliptin, saxagliptin, sitagliptin, and vildagliptin [1,16,23]. On the contrary, several inhibitors were reported as noncompetitive inhibitors in vitro [21,24], which indicated the availability of allosteric sites in the DPP4 binding pocket [24].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that caffeic acid started escaping the active site at the simulation time of 1.5 ns to occupy more stable interactions in the plausible sites. Hence, caffeic acid might never interacte stably in the DPP-4 active site and might be a non-competitive inhibitor of DPP-4 as several non-competitive inhibitors, as previously reported [40][41][42].…”
Section: Molecular Dynamics and Interaction Hotspot Identifications O...mentioning
confidence: 59%
“…Tables 1 and 2 show that throughout the simulation, caffeic acid interacted with amino acid residues of Lys463 (47.50%) and Trp62 (12.57%) dominantly. Our investigations found that Lys463 forming an hydrophobic interaction and Trp62 forming an aromatic edge-to-face interaction were considered as the interaction hotspots located in the DPP-4 From this simulation time, it could be seen that the RMSD LigMove value increased gradually along the simulation time until it reached 3.0 ns with an RMSD value of 18.158 Å while caffeic acid was no longer interacting with amino acid residues in the active side, revealing the availability of allosteric sites [40]. Even though there was a decreasing RMSD value reaching 9.209 Å at a simulation time of 5.7 ns, caffeic acid remained interacted in a plausible allosteric site.…”
Section: Molecular Dynamics and Interaction Hotspot Identifications O...mentioning
confidence: 98%